2018
DOI: 10.1002/adhm.201800908
|View full text |Cite
|
Sign up to set email alerts
|

Gels without Vapor Pressure: Soft, Nonaqueous, and Solvent‐Free Supramolecular Biomaterials for Prospective Parenteral Drug Delivery Applications

Abstract: now making up 90% of the drugs in development. [9] Since hydrogel matrices are predominantly hydrophilic with high water content, there may be limits in loading clinically relevant concentrations of poorly water-soluble APIs and achieving bolus-free, prolonged, zero or first-order release kinetics of these drugs over several weeks. [11] Further challenges include the mechanical fragility of many biodegradable hydrogels, dehydration over time, and nonideal drug release due to leakage or phase separation. [12] A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 113 publications
0
14
0
Order By: Relevance
“…The development of robust and facile synthetic materials for applications into bioelectronics, optogenetics, 3D cell culture, and drug delivery is an active field of research. In particular, well defined synthetic materials that possess biophysical, mechanical, and electrical mimicry of tissue are of wide interest for applications such as machine–brain interfaces .…”
mentioning
confidence: 99%
“…The development of robust and facile synthetic materials for applications into bioelectronics, optogenetics, 3D cell culture, and drug delivery is an active field of research. In particular, well defined synthetic materials that possess biophysical, mechanical, and electrical mimicry of tissue are of wide interest for applications such as machine–brain interfaces .…”
mentioning
confidence: 99%
“…We found that it was possible to monitor the interfacial concentration of rhodB with UV-Vis spectroscopy. Interestingly, we observed a large bolus release of the water-soluble drug from the hydrophobic phase to the hydrophilic phase at the interface until the same concentration was reached, subsequently an equilibrium or pseudosteady-state concentration was reached after 14 h. Such a system is potentially useful in modeling mass transfer of drugs between hydrophobic drug delivery materials into hydrophilic physiological conditions 25 .…”
Section: Resultsmentioning
confidence: 86%
“…20 A key challenge in developing drug cocktails is in their delivery because drugs have different therapeutic windows requiring different release kinetics. 21,22 The ability to independently Fig. 3 Prediction performance for leave-one-out experiments for environmental parameters only.…”
Section: Resultsmentioning
confidence: 99%